Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I asked a similar question before, but now I can formulate it more concretely. I am trying to perform an expansion of the function $$f(x) = \sum_{n=1}^{\infty} \frac{K_2(nx)}{n^2 x^2},$$ for $x \ll 1$. Here, $K_2(x)$ is the modified Bessel function of the second kind. This series is a result of solving the integral $$f(x) = \frac{1}{3}\int_1^\infty \frac{(t^2-1)^{3/2}}{\mathrm{e}^{xt}-1}\mathrm{d}t.$$ The stated result is $$f(x) \approx \frac{\pi^4}{45 x^4} - \frac{\pi^2}{12 x^2}+\frac{\pi}{6x}-\frac{1}{32}\left( \frac{3}{2}-2\gamma+2\ln4\pi-\ln x^2\right)+\mathcal{O}(x^2),$$ where $\gamma$ is the Euler-Mascheroni constant. It agrees numerically with $f(x)$ for small $x$. However, by using the series expansion of the Bessel function $$K_2(nx) = \frac{2}{n^2x^2}-\frac{1}{2}+\frac{1}{2}\sum_{k=0}^\infty \left[\psi(k+1)+\psi(k+3)-\ln\frac{n^2x^2}{4}\right]\frac{\left(\frac{n^2 x^2}{4}\right)^{k+1}}{k!(k+2)!},$$ with $\psi(x)$ being the digamma function and using the zeta regularization for summation over $n$, I am able to reproduce all the terms except $\frac{\pi}{6x}$. I.e., my result is $$f(x) = \frac{2\zeta(4)}{x^4} - \frac{\zeta(2)}{2x^2} + \frac{1}{8}\sum_{k=0}^\infty \left[\left(\psi(k+1)+\psi(k+3)-\ln\frac{x^2}{4}\right)\zeta(-2k) + 2 \zeta'(-2k)\right]\frac{\left(\frac{x^2}{4}\right)^{k}}{k!(k+2)!}.$$ It seems very strange that the $\frac{\pi}{6x}$ term should appear in the expansion since only even powers of $x$ appear in $K_2(nx)$. But, numerically, it is certainly there. How did I miss it?

Edit #1: I just got an idea where the $\frac{\pi}{6x}$ term might come from! Approximating the integral representation of $f(x)$ for $xt \ll 1$ and using the UV regulator $\Lambda$, we have $$f(x) \approx \frac{1}{3} \int_1^\Lambda \frac{(t^2-1)^{3/2}}{xt}\mathrm{d}t \approx \frac{\Lambda^3}{9x} - \frac{\Lambda}{2x} + \frac{\pi}{6x}.$$ OK, so now the question is why doesn't the Bessel series see this term and what to do about it?

Edit #2: The missing term might indicate that the zeta regularization isn't used properly. The term $\frac{\pi}{6x}$ appears right in the middle, separating the convergent sums $\zeta(4)$ and $\zeta(2)$ from the (regularized) divergent sums $\zeta(-2k)$ and $\zeta'(-2k)$. So, the missing term may be the price to pay for using the zeta regularization. Unfortunately, I don't know enough math to come to any decisive conclusion.

Edit #3: In edit #1 I argued that the missing term $\frac{\pi}{6x}$ comes from expansion of the exponential in the denominator. When I expand the numerator in the binomial series $$f(x) = \frac{1}{3} \int_1^\infty \frac{t^3}{\mathrm{e}^{xt}-1}\sum_{k=0}^\infty \binom{3/2}{k}(-t^{-2})^k\mathrm{d}t$$ and perform the integration, I again obtain my original result without $\frac{\pi}{6x}$. So, depending on what I choose to expand, I obtain different (incomplete) results??

share|cite|improve this question
up vote 4 down vote accepted

Using Mellin transforms we can find the asymptotics in an intuitive and straightforward manner. We have that $$ \mathfrak{M}(K_2(x)/x^2; s) = 2^{s-4} \Gamma(s/2) \Gamma(s/2-2),$$ so that viewing $f(x)$ as a harmonic sum, we get $$ \mathfrak{M}(f(x); s) = f^*(s) = 2^{s-4} \Gamma(s/2) \Gamma(s/2-2) \zeta(s).$$ Now invert to get the expansion of $f(x).$ I will give a table of the contributions from the poles down to the pole at $s=-6.$ $$ \begin{array} \operatorname{Res}(f^*(s) \, x^{-s}; s=4) & = & 1/45\,{\frac {{\pi }^{4}}{{x}^{4}}} \\ \operatorname{Res}(f^*(s) \, x^{-s}; s=2) & = & -1/12\,{\frac {{\pi }^{2}}{{x}^{2}}} \\ \operatorname{Res}(f^*(s) \, x^{-s}; s=1) & = & 1/6\,{\frac {\pi }{x}} \\ \operatorname{Res}(f^*(s) \, x^{-s}; s=0) & = & -1/16\,\ln \left( 4\,\pi \right) +1/16\,\gamma+1/16\, \ln \left( x \right) -{\frac {3}{64}} \\ \operatorname{Res}(f^*(s) \, x^{-s}; s=-2) & = & {\frac {1}{96}}\,\zeta \left( 1,-2 \right) {x}^{2} \\ \operatorname{Res}(f^*(s) \, x^{-s}; s=-4) & = & {\frac {1}{3072}}\,\zeta \left( 1,-4 \right) {x}^{4} \\ \operatorname{Res}(f^*(s) \, x^{-s}; s=-6) & = & {\frac {1}{184320}}\,\zeta \left( 1,-6 \right) {x}^{6}. \end{array}$$ As to how the Mellin transform of $K_2(x)$ is calculated, I can offer some ideas. Start with the known integral representation $$K_\alpha(x) = \int_0^\infty e^{-x \cosh t} \cosh (\alpha t) \; dt,$$ so that $$\mathfrak{M}(K_2(x); s) = \int_0^\infty \int_0^\infty e^{-x \cosh t} \cosh (2t) \; dt \; x^{s-1} \; dx.$$ This becomes $$ \int_0^\infty \cosh (2t) \int_0^\infty e^{-x \cosh t} x^{s-1} \; dx \; dt = \Gamma(s) \int_0^\infty \frac{\cosh (2t)}{(\cosh t)^s} dt.$$ Now using $$\cosh(2t) = 2\cosh(t)^2 - 1,$$ we obtain $$ \Gamma(s) \left(2 \int_0^\infty \frac{1}{(\cosh t)^{s-2}} dt - \int_0^\infty \frac{1}{(\cosh t)^s} dt \right).$$ Furthermore, $$ \int_0^\infty \frac{1}{(\cosh t)^s} dt = 2^s \int_0^\infty \frac{1}{(e^t + e^{-t})^s} dt = 2^s \int_0^\infty \frac{1}{e^{ts}} \frac{1}{(1 + e^{-2t})^s} dt$$ which is $$ 2^s \int_0^\infty \frac{1}{e^{ts}} \sum_{q\ge 0} (-1)^q \binom{q+s-1}{q} e^{-2qt} dt = 2^s \int_0^\infty \sum_{q\ge 0} (-1)^q \binom{q+s-1}{q} e^{-(2q+s)t} dt $$ or $$ 2^s \sum_{q\ge 0} (-1)^q \binom{q+s-1}{q} \int_0^\infty e^{-(2q+s)t} dt = 2^s \sum_{q\ge 0} (-1)^q \binom{q+s-1}{q} \frac{1}{2q+s}.$$ Now this last term is $$ 2^s \frac{1}{s} \; _2F_1(s/2, s; 1+s/2; -1). $$ But we have $$ _2F_1(a, 2a; a+1; -1) = \frac{1}{2a} \frac{\Gamma(a+1)^2}{\Gamma(2a)}$$ as can be seen e.g. here.

Hence $$\int_0^\infty \frac{1}{(\cosh t)^s} dt = 2^s \frac{1}{s^2} \frac{\Gamma(s/2+1)^2}{\Gamma(s)}.$$ Concluding, we have shown that $$\mathfrak{M}(K_2(x);s) = 2 \Gamma(s) 2^{s-2} \frac{1}{(s-2)^2} \frac{\Gamma(s/2)^2}{\Gamma(s-2)} - \Gamma(s) 2^s \frac{1}{s^2} \frac{\Gamma(s/2+1)^2}{\Gamma(s)} \\ = 2^{s-1} \frac{s-1}{s-2}\Gamma(s/2)^2 - 2^s \frac{1}{s^2} \Gamma(s/2+1)^2 = 2^{s-1} \frac{s-1}{s-2}\Gamma(s/2)^2 - 2^{s-2} \Gamma(s/2)^2 = 2^{s-2} \Gamma(s/2)^2 \left( 2 \frac{s-1}{s-2} - 1\right) = 2^{s-2} \Gamma(s/2)^2 \frac{s}{s-2} = 2^{s-2} \Gamma(s/2)^2 \frac{s/2}{s/2-1} = 2^{s-2} \Gamma(s/2+1) \Gamma(s/2-1).$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.